Sildenafil (Viagra) Protective Effects on Neuroinflammation: The Role of iNOS/NO System in an Inflammatory Demyelination Model - Catarina Raposo; Ana Karolina de Santana Nunes; Rayana Leal de Almeida Luna; Shyrlene Meiry da Rocha Araújo; Maria Alice da Cruz-Höfling; Christina Alves Peixoto (Mediators of Inflammation)
We recently demonstrated that sildenafil reduces the expression of cytokines, COX-2, and GFAP in a demyelinating model induced in wild-type (WT) mice. Herein, the understandings of the neuroprotective effect of sildenafil and the mediation of iNOS/NO system on inflammatory demyelination induced by cuprizone were investigated. The cerebella of iNOS−/− mice were examined after four weeks of treatment with cuprizone alone or combined with sildenafil. Cuprizone increased GFAP, Iba-1, TNF-α, COX-2, IL-1β, and IFN-γ expression, decreased expression of glutathione S-transferase pi (GSTpi), and damaged myelin in iNOS−/− mice. Sildenafil reduced Iba-1, IFN-γ, and IL-1β levels but had no effect on the expression of GFAP, TNF-α, and COX-2 compared to the cuprizone group. Sildenafil elevated GSTpi levels and improved the myelin structure/ultrastructure. iNOS−/− mice suffered from severe inflammation following treatment with cuprizone, while WT mice had milder inflammation, as found in the previous study. It is possible that inflammatory regulation through iNOS-feedback is absent in iNOS−/− mice, making them more susceptible to inflammation. Sildenafil has at least a partial anti-inflammatory effect through iNOS inhibition, as its effect on iNOS−/− mice was limited. Further studies are required to explain the underlying mechanism of the sildenafil effects.